Comprehensive Clinical and Molecular Analysis of 12 Families with Type 1 Recessive Cutis Laxa. Issue 1 (13th August 2012) - Callewaert, Bert; Su, Chi‐Ting; Van Damme, Tim; Vlummens, Philip; Malfait, Fransiska; Vanakker, Olivier; Schulz, Bianca; Mac Neal, Meghan; Davis, Elaine C.; Lee, Joseph G.H.; Salhi, Aicha; Unger, Sheila; et al.
<x xml:space="preserve">Abstract</x> Autosomal recessive cutis laxa type I (ARCL type I) is characterized by generalized cutis laxa with pulmonary emphysema and/or vascular complications. Rarely, mutations can be identified in FBLN4 or FBLN5. Recently, LTBP4 mutations have been implicated in a similar phenotype. Studying FBLN4, FBLN5, and LTBP4 in 12 families with ARCL type I, we found bi‐allelic FBLN5 mutations in two probands, whereas nine probands harbored biallelic mutations in LTBP4. FBLN5 and LTBP4 mutations cause a very similar phenotype associated with severe pulmonary emphysema, in the absence of vascular tortuosity or aneurysms. Gastrointestinal and genitourinary tract involvement seems to be more severe in patients with LTBP4 mutations. Functional studies showed that most premature termination mutations in LTBP4 result in severely reduced mRNA and protein levels. This correlated with increased transforming growth factor‐beta (TGFβ) activity. However, one mutation, c.4127dupC, escaped nonsense‐mediated decay. The corresponding mutant protein (p.Arg1377Alafs*27) showed reduced colocalization with fibronectin, leading to an abnormal morphology of microfibrils in fibroblast cultures, while retaining normal TGFβ activity. We conclude that LTBP4 mutations cause disease through both loss of function and gain of function mechanisms.